REFINEMENT OF THE PARAMETERS OF A MATHEMATICAL MODEL OF QUADCOPTER DYNAMICS - Adalat PASHAYEV; Elkhan SABZIEV (Scientific Journal of Silesian University of Technology. Series Transport)
Errors in the calculation of the parameters of quadcopter control models at design stage significantly change the desired aerodynamic properties of the drone and make it difficult to control its flight along the intended path. Therefore, to calculate the adequate operation modes of the blades, it becomes necessary to refine some parameters of the mathematical model of the drone as accurately as possible. This paper shows the possibility of using control parameters (rotational speed of the blades) and information received from navigation devices of the drone to refine the values of the parameters of the mathematical model of the drone. For this purpose, a mathematical model of a quadcopter is built, and the problem of refining the parameters of its dynamic model is investigated based on the information received from navigation devices and the control parameters in the initial period of its flight. From the results obtained from several consecutive measurements, a system of equations expressing a mathematical model is solved. The mean value of the corresponding solutions of the system of three-dimensional linear equations obtained at different time intervals is the refined value of the parameters.